2014
DOI: 10.1188/14.onf.350-359
|View full text |Cite
|
Sign up to set email alerts
|

Awaiting Diagnosis of Breast Cancer: Strategies of Enduring for Preserving Self

Abstract: The Praxis Theory of Suffering enables nurses to recognize and respond according to the behaviors of suffering, and to endure with healthy, adaptive, and normalizing behaviors that enable preserving self.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 38 publications
0
27
0
5
Order By: Relevance
“…16,17 When enduring, the person suppresses emotion in order to 'keep going', to cognitively suppress the fear of cancer, until able to accept the notion (or 'come to terms') that they may indeed have cancer. 9 This state of emotional suppression is evident behaviourally. When the enduring is 'acute', sufferers walk stiffly and upright, without spontaneous movement.…”
Section: Understanding Suffering Behavioursmentioning
confidence: 99%
See 2 more Smart Citations
“…16,17 When enduring, the person suppresses emotion in order to 'keep going', to cognitively suppress the fear of cancer, until able to accept the notion (or 'come to terms') that they may indeed have cancer. 9 This state of emotional suppression is evident behaviourally. When the enduring is 'acute', sufferers walk stiffly and upright, without spontaneous movement.…”
Section: Understanding Suffering Behavioursmentioning
confidence: 99%
“…I have conducted a large number of qualitative studies with 'distressed' patients, including those undergoing diagnosis for breast cancer and those who were dying from cancer, 9 and conducted qualitative synthesis of interrelated projects, a technique called theoretical coalescence, 15 fitting these studies together, to form the Praxis Theory of Suffering. 16,17 The clinical validity of the Distress Thermometer Recently, there has been a trend towards measuring 'distress' in cancer patients using the Distress Thermometer.…”
Section: Applying Qualitative Theory To Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Des études ont montré que les femmes en processus de dépistage d'un cancer du sein vivent beaucoup d'anxiété et d'incertitude pendant la phase de diagnostic, même lorsque l'affection se révèle bénigne. (Harding, 2014;Liao, Chen, Chen et Chen, 2008;Meechan, Collins, Moss-Morris et Petrie, 2005;Morse et al, 2014). Pendant cette période, le besoin d'information des femmes au sujet du processus d'évaluation diagnostique n'est pas toujours satisfait, ce qui risque d'amplifier le sentiment d'incertitude (Harding et McCrone, 2013;Liao, Chen, Chen et Chen, 2007).…”
unclassified
“…Studies have found that women undergoing investigation for breast cancer experience high levels of anxiety and uncertainty during the diagnostic phase, including the many women whose results are benign (Harding, 2013;Liao, Chen, Chen, & Chen, 2008;Meechan, Collins, Moss-Morris, & Petrie, 2005;Morse et al, 2014). Women undergoing investigation also have unmet informational needs about the diagnostic process that may increase this uncertainty (Harding & McCrone, 2013;Liao, Chen, Chen, & Chen, 2007).…”
Section: Introductionmentioning
confidence: 99%